The Truth behind the Text: the Study of the Qur’an with the Hikmah Approach - Syamsul Kurniawan (Graduate Program of Pontianak Institute of Islamic Studies, 2014)
Book Review: Dr. Syarif, MA., The Truth behind the Text: the Study of the Qur’an with the Hikmah Approach, Yogyakarta: Nusa Media, 2013. O you who believe, why do you say what you do not do? (3) It is severely hate¬ful in Allah’s sight that you say what you do not do. (QS. As-Saff: 2-3) What is true behind the text is what Dr. Syarif tried to explain in his book, Ap¬pearance behind the Text: the study of the Qur’an with the Hikmah Approach. In this book, one will find many terms on texts that have been examined by some experts of Qur’anic interpretation on the literal aspects, but did not in¬troduce the meaning of what is really meant by the text.